CUTTING TOOL LIFE AND ITS EFFECT ON SURFACE ROUGHNESS WHEN TURNING WITH WC-6% CO - Bendifallah, Mourad; Brioua, Mourad; Belloufi, Abderrahim (International Journal of Modern Manufacturing Technologies, 2020)
During turning operations, tool-part-chip contact causes wear to the cutting tool. The objective of this work is to study the wear of the clearance faces of tungsten carbide cutting tools during turning operations. Experimental tests on tool life for dry turning operations were carried out at four different cutting speeds, where the feed rate and the depth of cut are kept at constant values: 0.08 mm/rev for feed rate and 0.5 mm for depth of cut. An analysis of the influence of cutting parameters on the tools wear and consequently tool life (Τ) was presented, then the roughness of the machined surface Ra and the morphology of the chips produced were studied. This study makes it possible to identify that the wear mechanisms and the tool life are strongly linked to the roughness of the machined surfaces and to the morphology of the chips produced during the turning operations.